Standardization of SYBR Green-Based Real-Time PCR Through the Evaluation of Different Thresholds for Different Skin Layers: An Accuracy Study and Track of the Transmission Potential of Multibacillary and Paucibacillary Leprosy Patients - Sevilha-Santos, Lais; Cerqueira, Selma Regina Penha Silva; Gomes, Ciro Martins (Frontiers in Microbiology, 2021)
The development of new molecular techniques is essential for the early diagnosis of leprosy. Studies in the field have failed to elucidate the performance of these tests in clinical practice. We aimed to design a new primer pair for the repetitive element (RLEP) target of Mycobacterium leprae and to test the accuracy of SYBR green-based real-time PCR through the evaluation of different thresholds for different skin layers. We also aimed to track the transmission potential of multibacillary and paucibacillary leprosy patients. The in vitro validation of our reaction resulted in a quantification limit of 0.03 bacilli. We then conducted a cross-sectional/cohort-based study of diagnostic accuracy. Patients were included, and skin samples were divided into 4 layers: epidermis, superior dermis, inferior dermis and hypodermis. We also quantified M. leprae in nasal swabs of the included patients and compared the results to the number of household contacts also diagnosed with leprosy. One hundred patients with a clinical presentation compatible with leprosy were allocated to the leprosy or control group. Although the parasite load was greater in the superior and inferior dermis, M. leprae DNA was found in all skin layers. The best sensitivity was observed for the superior dermis using the presence of any quantifiable bacillus DNA as the threshold (sensitivity = 59.26% (95% CI = 45.97-71.32)). In the epidermis, setting 1 quantifiable bacillus as the threshold resulted in 100% specificity (95% CI = 92.29-100). The number of bacilli found in nasal swabs was not significantly related to the number of household contacts also diagnosed with leprosy. Paucibacillary patients tested positive only for bacillus fragments in nasal swabs but not for the entire bacilli. We can conclude that superficial biopsies might result in sensitivity loss, although different skin sample types will have little influence on the final accuracy. In contrast, threshold changes greatly influence these properties. Paucibacillary patients may not be a relevant source of disease transmission.